PENGARUH EMPLOYEE ENGAGEMENT DAN QUALITY OF WORK LIFE TERHADAP KINERJA KARYAWAN (Pada Karyawan Bagian Produksi PR. Trubus Alami Sidorejo Kab Malang) - Muhammad Mufti Hadzar Al Hawasyi; Hadi Sunaryo; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis study aims to examine and analyze the Effect of Employee Enggement, Quality Of Work Life and Work on the Performance of Production Section Employees in Public Relations. Trubus Alami Kab. Malang both partially and simultaneously. In this study the population amounted to 85 employees and all were taken as samples. Data collection through questionnaires, data analysis in this study using SPSS version 22. The sampling technique uses quantitative methods, while the data testing techniques used in this study include validity test, reliability test, classic assumption test, multiple linear regression analysis, and testing the research hypothesis. The results of the analysis show that partially or simultaneously the work environment, work discipline and work motivation have a positive and significant effect on employee performance on public relations. Trubus Alami Kab. Malang.Keywords : Employee Engagement, Quality of Work Life and Employee Performance